2011
DOI: 10.4081/ijas.2011.e20
|View full text |Cite
|
Sign up to set email alerts
|

Thyme (Thymus vulgaris) extract consumption darkens liver, lowers blood cholesterol, proportional liver and abdominal fat weights in broiler chickens

Abstract: A study with 160-day-old broiler chickens was conducted to investigate the effects of Thymus vulgaris (Thyme) extract in drinking water on plasma cholesterol, triglyceride, high density lipoprotein (HDL-c), low density lipoprotein (LDL-c) and very low density lipoprotein (VLDL-c), proportional abdominal fat, liver weights and liver color index. The chickens were divided into four groups and received 0 (ZT), 0.2 (LT), 0.4 (MT) or 0.6% (HT) thyme extract from day one to day 42 of age. All the birds receiving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 22 publications
9
43
0
Order By: Relevance
“…The present results are in line with those reported by Abdulkarimi et al (2011), who found that thyme decreased liver weight due to bile acid deconjugation, and thus reduced fat absorption (Pourmahmoud et al 2013). …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present results are in line with those reported by Abdulkarimi et al (2011), who found that thyme decreased liver weight due to bile acid deconjugation, and thus reduced fat absorption (Pourmahmoud et al 2013). …”
Section: Discussionsupporting
confidence: 83%
“…There are three possible methods for the action of thymol: the first is a reduction of harmful microbiota; the second is a boosting of the antioxidant system due to polyphenol constituents (Abdulkarimi et al 2011); the third may be due to increasing feed utilisation and enhancing immunity (Ghazalah & Ali 2008). Thus, the improved feed utilisation of the TO_1 group in the present study may be due to the decrease in the pathogen microflora and thus improved gut ecology and/or increased digestibility of the nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypocholesterolemic and antihyperlipidemic effect of thyme may be due to the action of thymol and carvacrol on HMG-CoA reductase, the rate-limiting enzyme of cholesterol, which reduced fat absorption from the gut or the lipid catabolism for gluconeogenesis (El-Ghousein and AlBeitawi, 2009;Abdulkarimi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, medicinal plants are receiving lots of attention as feed additives (Abdulkarimi et al, 2011;, especially as natural antioxidants. Silybum marianum fruit extract has been reported to reduce the lipid concentration of the thigh muscle and to increase the muscle's resistance to oxidative stress in broilers (Schiavone et al, 2007).…”
Section: Introductionmentioning
confidence: 99%